Comparison of Estimation Techniques for Vibro-Acoustic Transfer Path Analysis - Paulo Eduardo França Padilha; José Roberto de França Arruda (Shock and Vibration)
Vibro-acoustic Transfer Path Analysis (TPA) is a tool to evaluate the contribution of different energy propagation paths between a source and a receiver, linked to each other by a number of connections. TPA is typically used to quantify and rank the relative importance of these paths in a given frequency band, determining the most significant one to the receiver. Basically, two quantities have to be determined for TPA: the operational forces at each transfer path and the Frequency Response Functions (FRF) of these paths. The FRF are obtained either experimentally or analytically, and the influence of the mechanical impedance of the source can be taken into account or not. The operational forces can be directly obtained from measurements using force transducers or indirectly estimated from auxiliary response measurements. Two methods to obtain the operational forces indirectly – the Complex Stiffness Method (CSM) and the Matrix Inversion Method (MIM) – associated with two possible configurations to determine the FRF – including and excluding the source impedance – are presented and discussed in this paper. The effect of weak and strong coupling among the paths is also commented considering the techniques previously presented. The main conclusion is that, with the source removed, CSM gives more accurate results. On the other hand, with the source present, MIM is preferable. In the latter case, CSM should be used only if there is a high impedance mismatch between the source and the receiver. Both methods are not affected by a higher or lower degree of coupling among the transfer paths.